2000
DOI: 10.1159/000047300
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of a Class IA Antiarrhythmic Drug on the Ventricular Evoked Response Amplitude in Patients with Cardiac Pacemakers

Abstract: Some newer cardiac pacemakers are able to control the efficacy of the ventricular pacing pulse beat by beat and to adjust the ventricular output to the actual pacing threshold. This capture verification is based on the detection of the ventricular evoked response amplitude, which has to be detected immediately after the pacing pulse. The sensitivity of the pacemaker to detect the evoked response amplitude must be adjusted individually to avoid the simultaneous detection of lead polarization. The aim of the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Activation of AutoCapture™ algorithm can be influenced by body position and exercise, 12 as well as by class IA antiarrhythmic drugs such as ajmaline, 13 but seems to be primarily affected by the mechanical properties rather than by the electrophysiology of the heart 8 . By definition, lead polarization is a hardware constant and is dependent on the surface material and structure of the lead, but might be influenced by changes at the contact area of the lead tip to the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AutoCapture™ algorithm can be influenced by body position and exercise, 12 as well as by class IA antiarrhythmic drugs such as ajmaline, 13 but seems to be primarily affected by the mechanical properties rather than by the electrophysiology of the heart 8 . By definition, lead polarization is a hardware constant and is dependent on the surface material and structure of the lead, but might be influenced by changes at the contact area of the lead tip to the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…The sensing of evoked response worked well, and the thresholds remained stable in those of our patients (n = 6) who were on chronic antiarrhythmic medication. The effect of antiarrhythmic drugs has been assessed with AutoCapture; ajmaline injection has decreased the evoked response amplitude for a few minutes after injection 13 . On the other hand, no significant effect was found on chronic ventricular pacing threshold after intravenous or oral administration of sotalol or propranolol 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Arrhythmias are common in patients with pacemakers and may require management with antiarrhythmic drugs (AADs), which may affect the cardiac conduction system (1)(2)(3). Previous studies (4)(5)(6)(7) have reported that some AADs affect atrial and ventricular pacing threshold and impedance.…”
Section: Introductionmentioning
confidence: 99%